Shyer fish are superior swimmers in Siberian sturgeon (Acipenser baerii) - Xiang, Lingli; Mi, Xiangyuan; Dang, Yingchao; Zeng, Yu; Jiang, Wei; Du, Hao; Twardek, William M.; Cooke, Steven J.; Bao, Jianghui; Duan, Ming (Frontiers in Marine Science, 2022)
Differences in individual personality are common amongst animals, which can play an ecological and evolutionary role, given links to fitness. Personality affects animal life processes and outputs (e.g., behaviour, life history, growth, survival, reproduction) and has become a common theme in animal behavioural ecology research. For fish, personality affects various behaviours (e.g., swimming), physiology, morphology, and thus the growth and survival of fish. In the present study, we used Siberian Sturgeon to explore how personality traits of boldness and shyness are related to swimming performance post-exercise recovery and phenotypic morphology. Firstly, our results indicated that the Siberian sturgeon juveniles of shyness were better swimmers, validating the evolutionary biology trade-off theory. The critical swimming speed (Ucrit) of the shy groups was higher than that of the bold groups. The proportion of time spent on countercurrent forward swimming in the shy groups (26%) was significantly lower than in the bold groups (41%). Secondly, the shy groups were more resilient after exercise fatigue, which may be the main reason for their superior swimming performance. The external behaviour showed that the swimming fatigue recovery ability of shy groups (R=104%) was greater than that of bold groups (R=95%). The intrinsic physiological performance showed that during the recovery period, the glucose and lactic acid concentration recovery ability of the shy groups was greater than that of the bold groups, and the total protein concentration was always higher than that of the bold groups. Thirdly, the shy groups were more streamlined, which may be another reason for their higher swimming performance. Compared with bold groups, shy groups had smaller caudate stalk lengths, caudate stalk heights, superior caudal lobes, and inferior caudal lobes. On the contrary, the head height, body height, snout thickness, snout length, and body length of shy groups were more extensive than that of the bold groups, which can minimise recoil energy loss and enhance stable swimming performance. This research further enriches the theoretical viewpoint in fish behaviour biology and provides an excellent example for studying the relationship between a sturgeon’s personality traits and swimming performance.